2014
DOI: 10.1007/s10549-014-3216-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the BEAT Cancer physical activity behavior change intervention on physical activity, aerobic fitness, and quality of life in breast cancer survivors: a multicenter randomized controlled trial

Abstract: Most breast cancer survivors (BCS) are not meeting recommended physical activity guidelines. Here, we report the effects of the Better Exercise Adherence after Treatment for Cancer (BEAT Cancer) behavior change intervention on physical activity, aerobic fitness, and quality of life (QoL). We randomized 222 post-primary treatment BCS to the 3-month intervention (BEAT Cancer) or usual care (UC). BEAT Cancer combined supervised exercise, face-to-face counseling, and group discussions with tapering to home-based e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
228
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 154 publications
(238 citation statements)
references
References 37 publications
9
228
0
1
Order By: Relevance
“…As previously reported, our 3-month physical activity behavior change intervention significantly increased the odds of meeting physical activity recommendations (primary outcome for this trial) (28). Measurement of sleep outcomes as a secondary study outcome provides the opportunity to further address the current knowledge gap by testing sleep outcomes in a larger trial (33).…”
Section: Introductionsupporting
confidence: 72%
“…As previously reported, our 3-month physical activity behavior change intervention significantly increased the odds of meeting physical activity recommendations (primary outcome for this trial) (28). Measurement of sleep outcomes as a secondary study outcome provides the opportunity to further address the current knowledge gap by testing sleep outcomes in a larger trial (33).…”
Section: Introductionsupporting
confidence: 72%
“…These findings are noteworthy because previous examinations of expressive writing interventions among non-Hispanic Whites have not reported improvements in quality of life [32]. Although the study sample lived in the USA for 18 years on average, the baseline quality of life indicated by FACT (M = 73.3) was low, compared with non-Hispanic White female cancer patients (normative value = 82.1) [33] and breast cancer survivors (M = 84.3) [34]. Perhaps, the significant unmet emotional needs among Chinese-speaking breast cancer survivors [35] render this underserved population more likely to experience the benefits of an intervention, suggesting the importance of conducting intervention studies in underserved populations both from scientific and clinical perspectives.…”
Section: Discussionmentioning
confidence: 66%
“…78 Among breast cancer survivors, supervised exercise as well as home-based exercise and telephone coaching have been successful in increasing physical activity levels, with increases seen up to 271 minutes/week. 79-81 Weight loss interventions, utilizing in person or telephone coaching have also been successful in this population with weight loss of up to 12.5 kg achieved. 82-84 These studies demonstrate the potential for health behavior modification following a DCIS diagnosis.…”
Section: An Opportunity For Interventionmentioning
confidence: 99%